Prevalence of Antibiotic Resistance to Isonicotinylhydrazide and Rifampicin in Culture Positive Pulmonary Tuberculosis Patients from 2014 to 2016 in Zahedan City, Iran - Seyed Mohammad Hashemi Shahri; Fatemeh Fardoust; Shokoufeh Mogharabi Ostad Kalayeh; Mohammad Ghenaatpisheh Sanani (Baqiyatallah University of Medical Sciences, 2019)
Background: One third of the world's population is infected with TB, and the disease is known as the second deadly global infection, even more severe than measles. The disease kills about 2 million people a year. Approximately 8 million people in the world are affected by advanced tuberculosis (TB). Objective: The current study aimed to determine the frequency of resistance to the antibiotics isoniazid and rifampin in positive culture pulmonary TB patients in Zahedan city during 2013-2016. Methods: This descriptive cross-sectional study studied 100 samples from patients who referred to Boo-Ali hospital of Zahedan city from 2014 to 2016. First, the isoniazid solution was prepared, and then the rifampin solution was prepared. After that, 200 μL of mycobacterium suspension was added to the antibiotic and antibiotic-free control. Results: Of 100 patients participating in the study, 50 (50%) were male and 50 (50%) were female. Participants had an average age of 51.69 ± 20.41 years (95-12 years), 79 (79%) were Iranians and 21 (21%) were Afghans. Of the 100 samples, 55 (55%) were from the year 2013, 21 (21%) were from 2014, 10 (10%) were from 2015, and 14 (14%) were from year 2016. The samples examined showed that 4 (4%) were resistant and 96% were sensitive. Conclusion: The results of the current study showed that out of 100 samples, 4 cases (4%) had resistance and 96% were sensitive; 2% were resistant to isoniazid, and 2% were resistant to isoniazid and rifampin.